Hyaluronan Is Not a Ligand but a Regulator of Toll-Like Receptor Signaling in Mesangial Cells: Role of Extracellular Matrix in Innate Immunity. (21st January 2014) - Ebid, Rainer; Lichtnekert, Julia; Anders, Hans-Joachim
Abstract : Glomerular mesangial cells (MC), like most cell types secrete hyaluronan (HA), which attached to the cell surface via CD44, is the backbone of a hydrophilic gel matrix around these cells. Reduced extracellular matrix thickness and viscosity result from HA cleavage during inflammation. HA fragments were reported to trigger innate immunity via Toll-like receptor-(TLR-) 2 and/or TLR4 in immune cells. We questioned whether HA fragments also regulate the immunostimulatory capacity of smooth muscle cell-like MC. LPS (TLR4-ligand) and PAM3CysSK4 (TLR2-ligand) induced IL-6 secretion in MC; highly purified endotoxin-free HA< 3000 Da up to 50  μ g/mL did not. Bovine-testis-hyaluronidase from was used to digest MC-HA into HA fragments of different size directly in the cell culture. Resultant HA fragments did not activate TLR4-deficient MC, while TLR2-deficient MC responded to LPS-contamination of hyaluronidase, not to produced HA fragments. Hyaluronidase increased the stimulatory effect of TLR2-/-3/-5 ligands on their TLR-receptors in TLR4-deficient MC, excluding any effect by LPS-contamination. Supplemented heparin suppressed every stimulatory effect in a dose-dependent manner. We conclude that the glycosaminoglycan HA creates a pericellular jelly barrier, which covers surface receptors like the TLRs. Barrier-thickness and viscosity balanced by HA-synthesis and degradation and the amount of HA-receptors on the cell surface regulate innate immunity via the accessibility of the receptors.